Hibah bertaʻlīq dan penggunaannya dalam takaful: Kajian dari perspektif fiqh / Mohd Kamil Ahmad - Mohd Kamil , Ahmad (2017)
Islamic jurists in general are in dissension on the permissibility of stipulating conditions in hibah. Although the majority do not allow the condition, but still there is opinion that validates it. Basing on the opinion that allows conditions in hibah, this study seeks to explore the suitability and limitations in the implementation of conditional hibah in takaful, especially in issues regarding the distribution of takaful benefit to particular nominee as chosen by takaful participant, issues of surplus sharing between takaful operator and participant, and methods of remunerating takaful agents for their sales. This study is qualitative in nature and it depends heavily on library research and document analysis. As a complementary, interview method is also used in order to obtain additional information pertaining the actual practices in the takaful industry. The findings suggest that the conditional hibah is a feasible concept and it is adoptable as a viable solution for the mentioned takaful issues. However, the implementation of this concept needs to be in line with several important rules. First: Any condition stipulated in hibah does not change its nature from tabarruʻ to muʻāwaḍah; if this happens, the special characteristic of hibah in which it is not affected by elements of riba, gharar, and jahālah, will no longer exist. Second: The stipulated condition does not change hibah into a form of contract with nearly similar characteristics, for example: a will or a juʻālah, as it is no longer a hibah and therefore has to submit to rules of the new contract.